Chemical composition of sorghum genotypes silages - Marielly Maria Almeida Moura; Daniel Ananias de Assis Pires; José Avelino Santos Rodrigues; Eleuza Clarete Junqueira de Sales; Renê Ferreira Costa; Daniella Cangussú Tolentino (Acta Scientiarum. Animal Sciences, 2016)
The objective was to select sorghum genotypes for silage production using its chemical characteristics. The experiment was carried out in the facilities of Embrapa Maize and Sorghum in Sete Lagoas, state of Minas Gerais, to evaluate the agronomic characteristics, and nutritional quality of silage of twelve sorghum genotypes. We used a randomized block design with three replications. In relation to the production of green matter, the genotypes SF15 Volumax and BR610 stood out (52.07; 48.00 and 41.87 ton ha-1). Regarding pH, genotypes 1015339, 1015347, 1016007, SF15, BRS655, Volumax and BR610 averaged 3.68. All genotypes were similar considering the nutritional value, ammonia nitrogen and water activity. The genotypes SF15, Volumax and BRS610 showed the highest productivity per area, representing the best options for silage production.